Is microdiffusion imaging able to improve the detection of cervical myelopathy? Study protocol of a prospective observational trial (MIDICAM-Trial) - Hohenhaus, Marc; Egger, Karl; Klingler, Jan-Helge; Hubbe, Ulrich; Reisert, Marco; Wolf, Katharina (BMJ open, 2019)
IntroductionThe diagnosis of degenerative cervical myelopathy (DCM) is difficult in numerous patients due to the limited correlation of clinical symptoms, electrophysiology and MRI. This applies especially for early disease stages with mild symptoms or in uncertainty due to comorbidities. Conventional MRI myelopathy signs show a restricted sensitivity to clinical symptoms of at most 60%. It is desirable to select patients for surgical treatment as early as possible before irreversible neurological damage occurs. To improve treatment, a more reliable imaging is necessary. Microdiffusion imaging (MIDI) is an innovative MRI modality to depict tissue alterations within one voxel based on diffusion-weighted imaging (DWI) postprocessing. By separating the affected area into several mesoscopic compartments, pathological changes might be detected more sensitive through this subtle tissue resolution. We hypothesise, that MIDI shows myelopathic alterations more sensitive than conventional MRI and improves the correlation to functional impairment.Methods and analysisIn this prospective, observational trial, 130 patients with a relevant degenerative cervical spinal stenosis receive MRI including MIDI and a standard clinical and electrophysiological assessment. Special subvoxel diffusion parameters are calculated. Clinical follow-ups are conducted after 3, 6 and with additional MRI and electrophysiology after 12 months. The primary endpoint is the sensitivity of MIDI to detect functional myelopathy defined by clinical and electrophysiological features correlated to conventional MRI myelopathy signs. Twenty healthy subjects will be included as negative control. The results will provide new insights into the development of mesoscopic spinal cord alterations in DCM associated to the clinical course. Aim is to improve the diagnostics of incipient myelopathy through this new modality.Ethics and disseminationThe study protocol is approved by the Ethics Committee of the University of Freiburg (reference 261/17). The results will be published in a peer-reviewed journal.Trial registration numberDRKS00012962.